Al buyu al aanhi anha - Lailatis Syarifah (Proceeding of Conference on Islamic Management, Accounting, and Economics, 2018)
This research aims to find out the reasons why some sales are baned in the time of the Prophet (peace and blessings of Allah be upon him). Knowing these reasons is important because it provides teachers or students with sufficient understanding to apply them to the sales contract that people are currently doing, so that they can do the right sales. The research found that the reasons for the prohibition due to two things are the causes of nodal and non-nodal causes. The nodal causes are either related to the contract place or the contract bundle. The reasons related to the place of contract are, firstly, not to be held on it; secondly, the holding of the contract is not considered as treasure or wealth; thirdly it should be non-existent, fourthly the seller should not be the owner of the sale; The reasons related to the contract bundle are riba and gharar. Non-contractual causes are damage and religious offense